Generation of Q-Switching pulse train with topology insulators / Nur Farhanah Zulkipli - Nur Farhanah , Zulkipli (2017)
This report presents two Q-switched Erbium-doped fiber lasers (EDFLs) utilizing topology insulators (TI) as saturable absorber (SA). The SA was fabricated by embedding Bismuth (III) Selenide (Bi2Se3) or Bismuth (III) Telluride (Bi2Te3) into a polyvinyl alcohol (PVA) film. The first Q-switched EDFL was obtained by incorporating a Bi2Se3 film inside the laser cavity. The laser generates stable pulse train by changing the pump power from 86.1 mW to 116.6 mW with repetition rate that can be tuned from 84.08 kHz to 87.03 kHz. It operated at 1559.8 nm wavelength with an excellent stability. The RF spectrum showed the signal noise to ratio of about 60 dB. The maximum pulse energy of 36.9 nJ and the lowest pulse width of 5.11 μs were obtained at pump power of 116.6 mW. The second Q-switched EDFL was demonstrated using TI Bi2Te3 material. The laser operates at 1558.5 nm with a lower threshold pump power of 25.0 mW. The repetition rate of the laser varies from 38.76 kHz to 77.88 kHz as the 980-nm pump power increased from 25.0 mW to 106.4 mW. The Q-switching operating has the shortest pulse width of 6.56 μs, the maximum pulse energy up to 127 nJ and the peak-to-pedestal ratio of 65 dB for the RF spectrum. These results shows that Bi2Te3 film performed better than Bi2Se3 one in terms of pulse energy and wider tuning range for repetition rate and pulse width. The experimental results also verify that both TI films possess the potential advantage for stable Q-switched pulse generation at 1.5 μm.